2012
DOI: 10.1097/tp.0b013e318246621d
|View full text |Cite
|
Sign up to set email alerts
|

Murine Islet Allograft Tolerance Upon Blockade of the B-Lymphocyte Stimulator, BLyS/BAFF

Abstract: In vivo BLyS neutralization effectively induces humoral tolerance and promotes long-term islet allograft survival in mice. Therefore, B-lymphocyte-directed immunotherapy targeting the homeostatic regulator, BLyS, may be effective in promoting transplantation tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…The B-cell activating factor is involved not only in survival but also in maturation of B cells [8], and it was suggested as a candidate biomarker of humoral rejection in animal models [9]. Nevertheless, recently in kidney transplant recipients no correlation between B-cell activating factor levels and antiehuman leukocyte antigen (HLA) antibody development was described [10], whereas an increased proportion of activated naïve B cells in kidney transplant recipients who develop anti-HLA antibodies was confirmed [10].…”
Section: Discussionmentioning
confidence: 96%
“…The B-cell activating factor is involved not only in survival but also in maturation of B cells [8], and it was suggested as a candidate biomarker of humoral rejection in animal models [9]. Nevertheless, recently in kidney transplant recipients no correlation between B-cell activating factor levels and antiehuman leukocyte antigen (HLA) antibody development was described [10], whereas an increased proportion of activated naïve B cells in kidney transplant recipients who develop anti-HLA antibodies was confirmed [10].…”
Section: Discussionmentioning
confidence: 96%
“…Post hoc analysis of the trial data demonstrated improvement in renal flare rates and reduction in proteinuria with anti-BAFF, with greatest benefit in those with high disease activity, suggesting efficacy in lupus nephritis, while serologic memory to past vaccine immunizations was preserved (163)(164)(165). It remains to be examined whether the beneficial effects of anti-BAFF in lupus are due to resetting aberrant checkpoints of peripheral B-cell tolerance eliminating autoreactive clones and/or attenuating T-cell activation by blocking costimulatory functions of BAFF (65,166).…”
Section: Role In Gnmentioning
confidence: 99%
“…However, these results were obtained in a globally immune cell depleted context ( scid mice). Results currently in press for mice illustrate the potential effectiveness of B cell depletion at transplant followed by periodic, gradually decreasing doses of anti-BLyS [115]. In this work, fully allogeneic transplanted pancreatic islets were maintained for more than 6 months after cessation of anti-BLyS treatment; moreover, subsequent new transplants of the same MHC haplotype were accepted and maintained.…”
Section: Resolve Revise and Relax: The 3 Rs Of Repertoire Adjustmentioning
confidence: 82%